Criminal and legal policy of Ukraine under martial law - Matsola, A.A. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
It is indicated that the full-scale armed aggression of the Russian Federation against Ukraine has led to the transformation of the security environment and the need for a systematic review of state policy, in particular in the criminal law sphere. Martial law requires the adaptation of criminal legislation to new challenges, effective counteraction to crimes against national security, territorial integrity and human rights. Criminal law policy is gaining strategic importance as a tool for protecting statehood and public values. The article examines the criminal and legal policy of Ukraine under martial law caused by the full- scale aggression of the Russian Federation. The adaptation of criminal legislation to new threats to national security, territorial integrity and citizens’ rights is considered. The author analyzes the functions of criminal and legal policy, its preventive, protective and stabilizing nature, emphasizing the need to combine the severity of measures with compliance with the principles of humanism, proportionality and the rule of law. Particular attention is paid to the legislative changes of 2022–2025, which increased responsibility for treason, collaboration, war crimes, looting and abuse of power, as well as the integration of national criminal law with international standards. The balance between state security and human rights guarantees is analyzed, as well as the prospects for the post-war transformation of criminal law policy, focused on the humanization of punishment, restorative justice, resocialization of offenders and integration into the European legal space. The conclusions emphasize that criminal law policy acts as a strategic element of state security, simultaneously ensuring the protection of society, strengthening the rule of law and restoring trust in justice in the context of war and post-war challenges. It is argued that the criminal legal policy of Ukraine under martial law is a special form of state policy in the field of security, aimed at ensuring the vitality of society, the defense capability of the state and the protection of fundamental human rights. Its essence lies in the combination of the functions of criminal legal regulation and ensuring national security, which necessitates the dynamic improvement of legislation in conditions of external aggression.